(untitled) (Práxis Educativa, 2024)
The objective of this article was to analyze the participation of Cesar Prieto Martinez, who served as General Inspector of Education in the state of Paraná, Brazil, from 1920 to 1924, in organizing the exhibitions of primary schools in the city of Curitiba, during the celebrations of the Independence Centennial in 1922. Cesar Prieto Martinez held this position from 1920 to 1924. The text is organized into two parts. The first part seeks to contextualize the political aspects surrounding his hiring to hold the position in Paraná, as well as providing a brief biography of Cesar Prieto Martinez, characterizing his credentials for the position of inspector. The second part, which is the main focus of this article, discusses Martinez’s role in organizing the School Exhibitions alluding to the Centennial of Independence in 1922. The theoretical frameworks used for analysis include: Chamon (2002), Moreno (2003), Rivière (1989) and Souza (2004). In addition to cultural history concepts, the study draws on the concept of rite as emphasized by Rivière (1989, 1997). The study consulted historiographical production on education during the period known as the First Republic, documents published by the school inspector found in the historical archive of the Public Archive of Paraná State, and newspapers of the time accessed through the Digital Newspaper Library of the National Library (called Hemeroteca). The research demonstrated Martinez’s performance in relation to the General Education Inspectorate Keywords: Cesar Prieto Martinez. School Exhibitions. Centennial of Independence.